Optimizing Aedes albopictus rearing: effects of insect- and bacteria-based larval diets on immature and adult performance - Eleni C. Savvidou; Georgios A. Kyritsis; Evangelia D. Mpakovasili; Stefania P. Kaltsou; Venetia Ch. Karathanasi; Antonios A. Augustinos; George Tsiamis; Christos I. Rumbos; Christos G. Athanassiou; Antonios Michaelakis; Nikos T. Papadopoulos (Scientific Reports)
Abstract Mass production of Aedes albopictus for Sterile Insect Technique (SIT) requires cost-effective and nutritionally balanced larval diets to ensure high survival, optimal development and competitive adult fitness. This study evaluates the potential of insect-derived meals and dead autoclaved bacteria as the main protein sources in mosquito larval diets. Four isoproteinic diets were studied, each one incorporating different protein sources: Brewer’s yeast (CAA), Tenebrio molitor meal (UTH-YM), Hermetia illucens meal (UTH-BSF) and Enterobacter spp. dry biomass (UTH-ENT). Results demonstrated immature survival higher than 78% for all diets. Developmental duration varied significantly across diets. The UTH-ENT diet extended larval development and conferred greater wing length. The highest protandry percentage was observed in the CAA diet, facilitating sex separation for SIT implementation. Adult survival over 20 days varied significantly among diets but not sexes. Males from the UTH-BSF diet exhibited the highest survival rate, while females from UTH-ENT diet showed the shortest lifespan. Given the rising costs and the variability in the quality of brewer’s yeast, our findings support the integration of insect-based diets as sustainable protein source alternatives for Ae. albopictus mass-rearing. Further research should refine larval diet formulations considering that combining different protein sources may enhance rearing success, to facilitate SIT efficiency and sustainable mosquito suppression.